Complementary medicine a costly risk in management of chronic knee osteoarthritis? A case report - Rampal, Sanjiv Rampal Lekhraj; Maniam, Sandra; Peh, Ho Yi; Feroze, Raghuman Sheriff; Singh Gill, Manvikram; Devaraj, Navin Kumar; Subbiah, Suresh Kumar (Universiti Putra Malaysia, 2021)
Knee osteoarthritis is the commonest cause of knee pain in the elderly. It is characterized by unresolved pain, limitation of motion and reduced quality of life. Total knee arthroplasty (TKA) is a safe and effective method in treating chronic knee osteoarthritis. We report a rare case of a seventy-seven-year-old Chinese female with multiple comorbidities and bilateral degenerative osteoarthritis who had sought services of traditional and complementary medicine (TCM) for pain relief. The patient experienced unresolved pain and superficial skin scars following the unregulated procedure. This paper aims to outline the importance of awareness among surgeons regarding the unregulated practice of TCM that may exacerbate chronic osteoarthritis, joint synovitis, influence the surgical approach for future procedures with the presence of scars and prosthetic joint infection risk.